Analisis Pengaruh Sikap, Norma Subjektif, Kontrol Perilaku dengan Religiusitas dan Niat sebagai Variabel Moderasi terhadap Keputusan Muzakki dalam Membayar Zakat - Arrosyid, Afif; Priyojadmiko, Eko (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2022)
This study aims to examine the role of moderation of religiosity and intention on the influence of attitudes, subjective norms, and behavioral control on muzakki decisions in paying zakat. By using the propotionate-stratified-random sampling technique, data from muzakki covering 277 respondents in 4 districts and 1 city in the Special Region of Yogyakarta were collected and analyzed using SEM (Structural Equation Modeling) WarpPLS 6.0. The results of this study indicate that attitudes, subjective norms, and behavior control have a positive and significant effect on compliance in paying zakat (all p-values ??are less than 0.05). Furthermore, apart from its role as a moderating variable, religiosity fails to directly influence the decision to pay zakat. Intention directly as a moderating variable affects muzakki's decision to pay zakat. In the relationship between moderating, independent and dependent variables, religiosity fails to moderate the influence of attitudes, subjective norms, and behavioral control on muzakki decisions in paying zakat. In further analysis, intention is shown to serve a moderate role of subjective attitudes and norms in their obedience to paying zakat, but intention does not show a moderating role on the effect of behavioral control on muzakki's decision to pay zakat.